Metabolic Rewiring in Radiation Oncology Toward Improving the Therapeutic Ratio - van Gisbergen, Marike W.; Zwilling, Emma; Dubois, Ludwig J. (Frontiers in Oncology, 2021)
To meet the anabolic demands of the proliferative potential of tumor cells, malignant cells tend to rewire their metabolic pathways. Although different types of malignant cells share this phenomenon, there is a large intracellular variability how these metabolic patterns are altered. Fortunately, differences in metabolic patterns between normal tissue and malignant cells can be exploited to increase the therapeutic ratio. Modulation of cellular metabolism to improve treatment outcome is an emerging field proposing a variety of promising strategies in primary tumor and metastatic lesion treatment. These strategies, capable of either sensitizing or protecting tissues, target either tumor or normal tissue and are often focused on modulating of tissue oxygenation, hypoxia-inducible factor (HIF) stabilization, glucose metabolism, mitochondrial function and the redox balance. Several compounds or therapies are still in under (pre-)clinical development, while others are already used in clinical practice. Here, we describe different strategies from bench to bedside to optimize the therapeutic ratio through modulation of the cellular metabolism. This review gives an overview of the current state on development and the mechanism of action of modulators affecting cellular metabolism with the aim to improve the radiotherapy response on tumors or to protect the normal tissue and therefore contribute to an improved therapeutic ratio.